Programa de informação profissional: Uma atividade de orientação profissional na escola. Análise de um guia curricular - Lobo, Stella Maris Alvares (2005)
The research report here presented is focused on the documental analysis of a curricular guide produced in the 70s by the Coordination of Studies and Pedagogical Norms (CENP Coordenadoria de Estudos e Normas Pedagógicas), organ connected to the State Bureau of São Paulo Education (SEESP Secretaria de Estado de Educação de São Paulo) to the activity entitled as Program of Professional Information (PIP Programa de Informação Profissional). It had been a compulsory activity from 1977 to 1982 for the first grades of what we used to call Secondary School (2º grau) in São Paulo state public schools. For this analysis, we have considered authors who deal with the relation between the school and the selection of cultural contents (Gimeno Sacristán and Forquin) and also authors who deal with the theme of the professional choice and information specific themes of the PIP activity from a critical perspective (Ferretti and Pimenta). The aim of this research is to verify, by means of the analysis of the legislation and, mainly of the existent material the curricular guide Programs of Professional Information as curricular component of the Secondary School Teaching , how the professional information had been presented to the school community, taking as indicators the selection of contents about the subject, the definition of goals, the proposition of activities and the bibliographical references, considering the Brazilian social political environment, from 1978 to 1982 years in which the activity had been part of the Secondary School teaching curricula. The results allow us not only to comprehend the analyzed proposal and its course in São Paulo school system, but also to provide elements to the comprehension of the activity of professional orientation in the current school.